Empowered elderly: Assistance in modifying urban elderly lifestyles from hypertension during the COVID-19 pandemic - Sundari, Fitriana (BKM Public Health and Community Medicine, 2021)
This study aims to develop a health improvement program for the elderly with hypertension during the COVID-19 pandemic. Based on the guidebook for elderly health services during the Ministry of Health's COVID-19 pandemic, posbindu sessions have been postponed. In addition, the lack of promotional media for the elderly during the COVID-19 pandemic causes an increased risk of hypertension among the elderly population. In achieving healthy, efficient, and independent elderly during in pandemic, it is necessary to improve health services for the elderly by making lifestyle modifications that adapt to the pandemic situation. The proposed program initiative is forming an elderly peer group in each RT, which is empowered by Posbindu cadres. In this program, several activities are formed, including basic health checks such as blood pressure, health consultations, health education, light exercise, sharing stories to increase the physical and mental health of the elderly. Health promotion activities are carried out in direct meetings at the RT level or monitoring by calling the elderly or their family using the telephone, especially those who live alone in their homes, to inquire about their health conditions. The challenge of this program is the commitment of Posbindu cadres, intensive posbindu cadres, and the condition of some older adults whose reception is slow so that it needs good preparation in planning this program. Posbindu cadres' empowerment to form elderly peer groups can be an alternative solution to improve the health of the elderly from hypertension during the COVID-19 pandemic.